Effect of Dietary Iron Level on Growth Performance and Enzyme Activity in Rohu (Labeo rohita Hamilton) Fingerlings - Chanda, S.; Samanta, A.; Paul, B. N.; Ghosh, K.; Giri, S. S. (Indian Journal of Animal Nutrition, 2017)
The present study was intended to evaluate the effect of different levels of dietary iron (Fe) on growth performasnce of rohu, Labeo rohita, fingerlings. Six isonitrogenous purified diets were formulated using casein, gelatin and dextrin as the major ingredients. Iron was supplemented at the levels of 0, 25, 75, 100 and 125 ppm in the form of ferrous sulphate (FeSO4. 7 H2O) in groups 1, 2, 3, 4, 5 and 6, respectively for 93 days. Rohu fingerlings in group 3 showed best performance in terms of weight gain (final weight 20.66Â±0.23 g), specific growth rate (0.64 g/d) and feed conversion ratio (1.08). Net weight gain (NWG) was higher (P<0.01) in group 3 containing 50 ppm of inorganic Fe beyond which NWG decreased (P<0.05). The activities of aspartate transaminase, alanine transaminase and alkaline phosphatase were in the physiological range for fish. Hence, supplementation of 50 ppm Fe in the diets showed better performance in rohu fingerlings, however, further studies are required to establish optimum Fe level in this species.